Long-Term Neurocognitive Outcomes in Sagittal Synostosis: The Impact of Reoperation. Issue 1 (January 2021) - Chuang, Carolyn; Chaunzwa, Tafadzwa L.; Wu, Robin; Singh, Anusha; Patel, Anup; Yang, Jenny F.; Hashim, Peter W.; Travieso, Roberto; Terner, Jordan S.; Mayes, Linda C.; Duncan, Charles C.; Jane, John A.; et al.
Abstract : Introduction: Optimal age at surgery in nonsyndromic sagittal craniosynostosis continues to be debated. Previous reports suggest that earlier age at whole vault cranioplasty more frequently requires reoperation. It is unknown, however, whether reoperation affects neurocognitive outcome. This study examined the impact of reoperation on neurocognitive outcome in children with nonsyndromic sagittal craniosynostosis using comprehensive neurocognitive testing. Methods: Forty-seven school-age children (age 5–16 years) with nonsyndromic sagittal craniosynostosis who underwent whole-vault cranioplasty were included in this analysis. Participants were administered a battery of standardized neuropsychological testing to measure neurocognitive outcomes. Results: Thirteen of the 47 participants underwent reoperation (27.7%); 11 out of the 13 reoperations were minor revisions while 2 reoperations were cranioplasties. Reoperation rate was not statistically different between patients who had earlier surgery (at age ⩽6 months) versus later surgery (at age >6 months) ( P > 0.05). Nonreoperated patients who had only one later-in-life surgery did not perform statistically better than reoperated patients on any outcome measure of neurocognitive function, including IQ, academic achievement, visuomotor integration, executive function, and behavior. Comparing reoperated earlier surgery patients with nonreoperated later surgery patients, reoperated earlier surgery patients had higher full-scale and verbal IQ ( P < 0.05), scored higher on word reading, reading comprehension, spelling, numerical operations, and visuomotor integration ( P < 0.05), and had fewer indicators of suspected learning disabilities ( P < 0.01) compared to nonreoperated later surgery patients. Conclusion: Reoperation rate after whole vault cranioplasty was 27.7%, with few cases of repeat cranioplasty (4.2% of all patients). Reoperation was not associated with worse neurocognitive outcome. Reoperated earlier surgery patients in fact performed better in IQ, academic achievement and visuomotor integration when compared to nonreoperated later surgery patients. Abstract : Supplemental Digital Content is available in the text